2022
DOI: 10.14814/phy2.15301
|View full text |Cite
|
Sign up to set email alerts
|

Liver vitronectin release into the bloodstream increases due to reduced vagal muscarinic signaling after cerebral stroke in female mice

Abstract: Vitronectin (VTN) is a glycoprotein enriched in the blood and activates integrin receptors. VTN blood levels increase only in female mice 24 h after an ischemic stroke and exacerbate brain injury through IL‐6‐driven inflammation, but the VTN induction mechanism is unknown. Here, a 30 min middle cerebral artery occlusion (MCAO) in female mice induced VTN protein in the liver (normally the main source) in concert with plasma VTN. Male mice were excluded as VTN is not induced after stroke. MCAO also increased pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…What is more, further analysis showed that PDE4B and PDE4D played a critical role in VTN-mediated ferroptosis. In addition to ferroptosis and cell differentiation, further investigation was needed to explore the other function of VTN in IBD in the future, including intestinal mucosal immunity, drug resistance, and intestinal fibrosis, and whether VTN regulated the phosphorylation of PDE4 in an integrin-dependent manner could be confirmed in next work, although the studies have confirmed that intergern was activated by VTN stimulation [ 26 , 47 , 48 ]. However, further studies are required to elucidate the mechanism regulating the VTN expression under physiological or pathological conditions, even whether there is a positive feedback loop between VTN-ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, further analysis showed that PDE4B and PDE4D played a critical role in VTN-mediated ferroptosis. In addition to ferroptosis and cell differentiation, further investigation was needed to explore the other function of VTN in IBD in the future, including intestinal mucosal immunity, drug resistance, and intestinal fibrosis, and whether VTN regulated the phosphorylation of PDE4 in an integrin-dependent manner could be confirmed in next work, although the studies have confirmed that intergern was activated by VTN stimulation [ 26 , 47 , 48 ]. However, further studies are required to elucidate the mechanism regulating the VTN expression under physiological or pathological conditions, even whether there is a positive feedback loop between VTN-ferroptosis.…”
Section: Discussionmentioning
confidence: 99%